(untitled) (Medico Legal Update, 2020)
Background: IL23R Polymorphisms appear to be engaged with several different types of autoimmune diseases such as psoriasis. Aim: We investigated the association of the Arg381Gln (R381Q) polymorphism in the IL23R gene with psoriasis risk in Babylon province. Methodology: The IL23R-gene variation Arg381Gln (R381Q) was performed using the programmable thermal cycler gradient PCR system. We investigated the association of IL23R gene variants with different clinic pathological features of psoriasispatients. Results: The allelic frequency of IL-23R Arg381Gln (R381Q) (rs11209026) gene showed that the frequency of AA genotype in patients with Psoriasis was more than in the control group (13 vs 8%) (OR = 2.222, CI 95% (0.476-10.357). In addition, this study suggests there is a statistical difference (P-valu>0.05) between (AG) and (AA) (P-value = 0.033),(AG) and (GG) (P-value = 0.012) genotypes in patients group compared to controls. The results also showed that the frequency of (G) Arg allele was (0.6) (0.62) in patients and control group respectively, and found no significant difference between (A) Gln and (G) Arg alleles in patients and controls (OR= 0.754), CI 95% (0.42-1.22). Conclusion: Our results showed no significant association of the IL-23R Arg381Gln (R381Q) (rs11209026) polymorphism with psoriasis patients susceptibility in Babylon province. The IL-23R Arg381Gln heterozygoteno significantly increases the risk and can’t be useful as a predisposing genetic marker.